Sports injuries and illnesses after implementation of the web-based surveillance system in world taekwondo - Jeong, H. S.; O'Sullivan, D. M.; Jeong, D. H.; Lee, S. Y. (Journal of Athletic Training, 2021)
Context Taekwondo epidemiology studies have been in short supply since the rule changes introduced by World Taekwondo in 2017.